The end of Shihabi rule in Lebanon 1841 AD. - العليوي, عبد الحميد (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The Research Talks About An Important Stage In The Modern History Of Lebanon, Specifically The End Of The First Half Of The Nineteenth Century, And The Research Explains How And The Reasons For The Collapse Of The Shihabi Rule In Lebanon, Including The Conflict And Wars That Took Place In The Levant As A Result Of The Problems That Arose Between The Egyptian Ruler Muhammad Ali Pasha And The Ottoman Empire, And Its Repercussions On Lebanon And The Internal Events That Took Place In It And The Repeated Revolutions Against The Egyptian Rule Until Its Departure From It In The Year 1841 AD, It Explains The Changes That Occurred In The Lebanese Arena After That As A Result Of The Repeated European Interference In The Ottoman Internal Affairs In Lebanon, As Well As The Result Of The Ottomans' Desire To Impose Direct Control Over Lebanon.